Trilobatin Protects Against Oxidative Injury in Neuronal PC12 Cells Through Regulating Mitochondrial ROS Homeostasis Mediated by AMPK/Nrf2/Sirt3 Signaling Pathway - Jianmei Gao; Jianmei Gao; Shuang Liu; Fan Xu; Yuangui Liu; Chun Lv; Yan Deng; Jingshan Shi; Qihai Gong (Frontiers in Molecular Neuroscience, 2018)
Oxidative stress-induced neuronal cell damage is a crucial factor in the pathogenesis of mitochondria-associated neurological diseases. Therefore, elimination of overproduction of mitochondrial reactive oxygen species (mtROS) may be a potential strategy for prevention and treatment of neurological diseases. In the present study, the neuroprotective effects of trilobatin (TLB), a novel small molecule monomer derived from Lithocarpus polystachyus Rehd, and its underlying mechanisms were investigated in vitro using hydrogen peroxide (H2O2)-induced oxidative stress model in a neuron-like PC12 cell. The findings revealed that pre-treatment with TLB dramatically concentration-dependently suppressed H2O2-induced PC12 cells damage by enhancing cell viability, repressed reduction of mitochondrial membrane potential (MMP) and decreased mtROS overgeneration, thereby deferring cell apoptosis. Further study demonstrated that TLB not only increased the enzymatic activities of glutathione peroxidase (GPx), isocitrate dehydrogenase 2 (IDH2),superoxide dismutase 2 (SOD2) and deacetylation of SOD2, but also activated silent mating-type information regulation 2 homolog 3 (Sirt3) within the mitochondria and thereby upregulating forkheadboxO3a (FoxO3a), which regulated mitochondrial DNA genes, then led to improving complex I activity and adenosine triphosphate (ATP) synthesis. What’s more, TLB up-regulated p-adenosine monophosphate-activated protein kinase (AMPK) level, the expression of peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1α), and ERRα. Intriguingly, TLB failed to mitigate H2O2-induced PC12 injury in the presence of the AMPK inhibitor (Compound C), indicating that the beneficial effects of TLB on the regulation of mtROS homeostasis were reliance on AMPK -Sirt3 signaling pathway. Moreover, TLB also facilitated nuclear factor erythroid 2-related factor 2 (Nrf2) and promoted antioxidant gene expression in turn, and knockdown of Nrf2 by siRNA dramatically reduced the neuroprotective effects of TLB. Notably, AMPK inhibitor abolished the activation of Nrf2 and Sirt3, whereas, knockdown of Nrf2 blocked the upregulation of Sirt3, but it did not affect p-AMPK level. In conclusion, our findings demonstrate that TLB protects against oxidative injury in neuronal PC12 cells through regulating mtROS homeostasis in the first time, which is, at least partly, mediated through the AMPK/Nrf2/Sirt3 signaling pathway.